ANALYSIS TA'ZIR PUNISHMENT AND ISTINBATH LEGAL METHOD IMAM MALIK'S PERSPECTIVE - Sufrizal Sufrizal; Muhammad Alwin Abdillah; M. Anzaikhan (Universitas Islam Negeri Ar-Raniry, 2023)
This study discusses the human ta'zir perspective of Imam Malik. Imam Malik argues that there is no minimum and maximum limit for uqubah / ta'zir punishment. It is well known in the Maliki madzhab, especially Imam Malik, that ta'zir punishment can exceed the limits of had punishment in some conditions and situations. Imam Malik once flogged a man who was found with a boy 400 lashes. Imam Malik's opinion is based on the actions of Umar bin Khatab r.a. where he flogged a man who faked Umar bin Khatab's ring to trick the baitul mal guard, with the aim of taking some of the baitul mal treasures. Caliph Umar at that time whipped him 100 times on the first, second and third day. If accumulated, umar bin khattab whipped the man 300 lashes. If we look at the istinbath method / method of determining the law used by Imam Malik r.a on this issue is to take the fatawa of the companions / mauquf hadith as a conceptual basis for determining the law and leave the Prophet's hadith which expressly prohibits the implementation of the ta'zir punishment beyond ten lashes. It is clearly seen in this problem that the characteristics of Imam Malik and his followers are very respectful of the words and actions of the companions even though at first glance they contradict the text.